Influenza A Virus: Phylogeny of Neuraminidase Primers and Amplification of Polymerase Basic Protein 2 and Neuraminidase Genes - MARIA OMEGA; RICHARD LAI; HANS HEINE; ROSS BARNARD (Microbiology Indonesia, 2009)
Influenza A virus is a highly contagious agent that causes bird flu. To date, 16 hemagglutinin (HA) and 9 neuraminidase (NA) subtypes are identified antigenically and can form any combinations or mutations with each other to confer non or low pathogenic to high pathogenic strains. Mutations in viral segments that are derived from avian isolates represent a novel subtypes to which human population is infected by influenza pandemics. In this work, polymerase basic protein 2 (PB2) gene segment of 8 different avian influenza subtypes were cloned to obtain more DNA samples for future work such as PB2 sequencing and to test HA primer annealing with PB2 gene. PCR amplification of NA gene segment of 3 different avian influenza subtypes was the second aim of this work to test primer universal for NA genes. Determination of the aligned sequences between 9 NA subtypes and NA primer PCR products was the second aim of this work, based on BLAST result homology 100% and phylogenetic trees of clustal